2020
DOI: 10.3389/fmech.2020.00061
|View full text |Cite
|
Sign up to set email alerts
|

FFT-Based Methods for Computational Contact Mechanics

Abstract: Computational contact mechanics seeks for numerical solutions to contact area, pressure, deformation, and stresses, as well as flash temperature, in response to the interaction of two bodies. The materials of the bodies may be homogeneous or inhomogeneous, isotropic or anisotropic, layered or functionally graded, elastic, elastoplastic, or viscoelastic, and the physical interactions may be subjected to a single field or multiple fields. The contact geometry can be cylindrical, point (circular or elliptical), o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(27 citation statements)
references
References 68 publications
0
26
0
Order By: Relevance
“…However, the convolution of integral ( 7) or ( 8) can be solved by the fast Fourier transform (FFT), which reduces the complexity greatly from o(N 4 ) to o(N 2 logN 2 ). This technique has been applied by many researchers [26]. Before carrying out the FFT, the matrix of the influence coefficient is usually constructed in the "convolution" form with the same dimension N × N.…”
Section: Methodsmentioning
confidence: 99%
“…However, the convolution of integral ( 7) or ( 8) can be solved by the fast Fourier transform (FFT), which reduces the complexity greatly from o(N 4 ) to o(N 2 logN 2 ). This technique has been applied by many researchers [26]. Before carrying out the FFT, the matrix of the influence coefficient is usually constructed in the "convolution" form with the same dimension N × N.…”
Section: Methodsmentioning
confidence: 99%
“…The discrete Fourier transforms of ICs are calculated from continuous ICs with the aliasing treatment [35,36]…”
Section: Dc-fft Algorithmmentioning
confidence: 99%
“…1. Compute the influence coefficients and treat the resulting series with zero-padding and wrap-around order, to accomplish the required circular nature [19] of the convolution series. 2.…”
Section: Application Of Dcfft To Semi-periodic Contact Problemsmentioning
confidence: 99%
“…This author [18] also applied spectral methods to simulate the contact process of viscoelastic materials in finite length line-contacts. Reviews on the application of the FFT in tribological modelling can be found in [10,19]. In the light of these recent developments in the spectral analysis of contact problems, two modifications of the state-of-the-art Discrete Convolution Fast Fourier Transform (DCFFT) algorithm are advanced in this paper.…”
Section: Introductionmentioning
confidence: 99%